2006
DOI: 10.1108/17410390610636850
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ERP systems on firm and business process performance

Abstract: The purpose of this article is to provide further insights into the adoption of enterprise resource planning systems (ERPS) and the impacts on organisational performance. It aims at challenging existing claims of ERP vendors with regards to the benefits of their products and at providing evidence of the benefits of bundling ERPS with supply chain management systems (SCMS). A survey was conducted to collect data on several aspects of organisational performance in companies which adopted ERPS, SCMS and the respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 18 publications
3
115
1
6
Order By: Relevance
“…Of the testing conducted, conflicting results have been found (e.g. Shang and Seddon [26] and Chand et al's [4] results show a positive impact, in conflict with the broader study conducted by Wieder et al [31]). Conflicting results, combined with the general lack of research in this field, result in this question being unanswered through the literature review.…”
Section: Do Erp Systems Have a Positive Impact On Organisational Perfcontrasting
confidence: 39%
“…Of the testing conducted, conflicting results have been found (e.g. Shang and Seddon [26] and Chand et al's [4] results show a positive impact, in conflict with the broader study conducted by Wieder et al [31]). Conflicting results, combined with the general lack of research in this field, result in this question being unanswered through the literature review.…”
Section: Do Erp Systems Have a Positive Impact On Organisational Perfcontrasting
confidence: 39%
“…Although the direct financial benefits and business performance of enterprise systems usage are still in controversy according to a series of studies conducted to investigate the enterprise system usage and organizational F o r P e e r R e v i e w performance (Hendricks et al 2007;Hitt et al 2002;Wieder et al 2006), most of them reported that enterprise systems usage cause positive impact on organizational operations by improving decision making processes, and most importantly, integrating information and resources of an organization into one system. Centralizing information and resources is thus identified as the most important factor for adopting enterprise systems.…”
Section: Security Concerns In Enterprise Information Systemsmentioning
confidence: 99%
“…The new IoT enabled enterprise systems extend the current systems and could gather more integrated data and information, bringing the security challenges to a new level. As most enterprise systems are installed inside organizations' intranets, the traditional security issues for enterprise systems mainly involve the identification process for users to access the system (Wieder et al 2006). However, the IoT enabled enterprise systems incorporate sensors into the enterprise systems and will involve more security challenges than the traditional enterprise systems because the data and information carried by the sensors might go beyond the enterprise system physically.…”
Section: Security Concerns In Enterprise Information Systemsmentioning
confidence: 99%
“…They found that there is existed improvement in performance of ERP adopters. In addition, Wieder, Booth, Matolcsy, and Ossimitz, (2006) examined the impact of ERP system on business process performance among Australian companies. Their results showed that there is no significant difference between ERP adopters and non-adopters.…”
Section: Enterprise Resource Planning (Erp) and Organizational Performentioning
confidence: 99%